CIRCADIAN VARIATION IN PERIPHERAL BLOOD LEUKOCYTES, THE PRIMARY IMMUNE CELLS, IN THE GARDEN LIZARD, CALOTES VERSICOLOR (DAUDIN) - TUMUL SINGH; RAMESH SINGH (The Bioscan, 2012)
The present study was undertaken to explore the circadian rhythmicity in leucocytes in Calotes versicolor (Daudin). Adult male lizards were acclimatized to the unconditioned laboratory for a week, lizards (N=5) were weighed, anaesthetized mildly and sacrificed at each of the following time point: 8 a.m., 12 noon, 04 p.m., 8 p.m., 12 midnight, 4 a.m. and 8 a.m. Blood was collected for determining Total Leukocyte Count (TLC) and Differential Leukocyte Count (DLC).During 24h, TLC ranged between 7.27 ± 1.32 to 12.05 ± 2.69; Monocyte (M) count between 2.22 ± 0.67 to 0.83 ± 0.11; Lymphocyte (L) count between 4.21 ± 1.03 to 2.15 ± 0.25. Amongst the granulocytes, basophil (B) count ranged between 1.83 ± 0.54 to 0.34 ± 0.10; eosinophil (E) count between 5.45 ± 1.36 to 0.40 ± 0.13; neutrophil (N) count between 2.48 ± 0.46 to 0.69 ± 0.28. However, cosinor analysis revealed that only one variable, eosinophil, exhibited statistically validated circadian rhythm; (plotted against 95% confidence limit), Acrophase being at 2040h.